The problems of utilization and autotractor tyre recovery in the context of ecological development of Ukraine - Кривоконь, Олександр Григорович (Eastern-European Journal of Enterprise Technologies, 2012)
The article tells about the methods of autotractor tires recovery, shows the effectiveness of some methods and inappropriate of others, reveals the features of the environmentally friendly process methods of restoration rubber products